RNAi in Piezodorus guildinii (Hemiptera: Pentatomidae): Transcriptome Assembly for the Development of Pest Control Strategies - Schvartzman, Claudia; Fresia, Pablo; Murchio, Sara; Mujica, María Valentina; Dalla-Rizza, Marco (Frontiers in Plant Science, 2022)
Red-banded stink bug Piezodorus guildinii (P. guildinii) has been described as the most damaging stink bug regarding soybean crops, leading to seed injury, low germination percentages, and foliar retention, at low population densities. In recent years, RNA interference (RNAi), a conserved eukaryote silencing mechanism has been explored to develop species-selective pesticides. In this work, we evaluated RNAi in P. guildinii to develop new pest-control strategies. For this, we assembled and annotated a P. guildinii transcriptome from a pool of all developmental stages. Analysis of this transcriptome led to the identification of 56 genes related to the silencing process encompassing siRNA, miRNA, and piRNA pathways. To evaluate the functionality of RNAi machinery, P. guildinii adults were injected with 28 ng/mg of body weight of double stranded RNA (dsRNA) targeting vATPase A. A mortality of 35 and 51.6% was observed after 7 and 14 days, respectively, and a downregulation of vATPase A gene of 84% 72 h post-injection. In addition, Dicer-2 and Argonaute-2 genes, core RNAi proteins, were upregulated 1.8-fold 48 h after injection. These findings showed for the first time that RNAi is functional in P. guildinii and the silencing of essential genes has a significant effect in adult viability. Taken together, the work reported here shows that RNAi could be an interesting approach for the development of red-banded stink bug control strategies.